2022
DOI: 10.1016/j.csbj.2022.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into apoptotic regulation of human Bfk as a novel Bcl-2 family member

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…These data suggest that positively selected and rapidly evolving genes have contributed to the divergence of cell death pathways in elephants. Among the rapidly evolving genes, for example, is CASP8 , the initiator caspase of extrinsic apoptosis, necroptosis, and pyroptosis (Boldin et al, 1996; Fritsch et al, 2019; Muzio et al, 1996), APAF1 , which forms the central scaffold of the apoptosome and and thus plays a critical role in apoptosis (Bratton and Salvesen, 2010; Cain et al, 2002), BOK an unusual BCL-2 family protein that directly induces mitochondrial outer membrane permeabilization (MOMP) and apoptosis in response to endoplasmic reticulum (ER) stress (Carpio et al, 2015; Llambi et al, 2016), BCL2L15 , another unusual BCL-2 family protein with pro-apoptotic functions that reduces malignant transformation of cells in the gastrointestinal tract (Dempsey et al, 2005; Jang et al, 2022; Özören et al, 2009) , BCLAP a tumor suppressor that induces cell cycle arrest at the G 1 /S and apoptosis through an uncharacterized but p53-independent mechanisms (Fan et al, 2011; Han et al, 2022; Yao et al, 2007; ZHAO et al, 2016), KDM6B , which promotes parthanatos by inhibiting DNA damage-evoked PARP-1 hyperactivation (Yang et al, 2022), and ALKBH7 is required for alkylation and oxidation-induced programmed necrosis (Fu et al, 2013; Jordan et al, 2017; Kulkarni et al, 2020). Remarkably, other cancer-resistant species have also evolved modified cell death pathways.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that positively selected and rapidly evolving genes have contributed to the divergence of cell death pathways in elephants. Among the rapidly evolving genes, for example, is CASP8 , the initiator caspase of extrinsic apoptosis, necroptosis, and pyroptosis (Boldin et al, 1996; Fritsch et al, 2019; Muzio et al, 1996), APAF1 , which forms the central scaffold of the apoptosome and and thus plays a critical role in apoptosis (Bratton and Salvesen, 2010; Cain et al, 2002), BOK an unusual BCL-2 family protein that directly induces mitochondrial outer membrane permeabilization (MOMP) and apoptosis in response to endoplasmic reticulum (ER) stress (Carpio et al, 2015; Llambi et al, 2016), BCL2L15 , another unusual BCL-2 family protein with pro-apoptotic functions that reduces malignant transformation of cells in the gastrointestinal tract (Dempsey et al, 2005; Jang et al, 2022; Özören et al, 2009) , BCLAP a tumor suppressor that induces cell cycle arrest at the G 1 /S and apoptosis through an uncharacterized but p53-independent mechanisms (Fan et al, 2011; Han et al, 2022; Yao et al, 2007; ZHAO et al, 2016), KDM6B , which promotes parthanatos by inhibiting DNA damage-evoked PARP-1 hyperactivation (Yang et al, 2022), and ALKBH7 is required for alkylation and oxidation-induced programmed necrosis (Fu et al, 2013; Jordan et al, 2017; Kulkarni et al, 2020). Remarkably, other cancer-resistant species have also evolved modified cell death pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, BCL-2 family Kin (BFK) is another example of a BCL-2like protein, which is structurally similar to BCL-G L [112]. A recently published report on BFK might shed light on the directions of further research on BCL-G [113]. Biophysical interaction analysis revealed that full-length BFK did not interact with other BCL-2-like Fig.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In this respect, BCL-2 family Kin (BFK) is another example of a BCL-2-like protein, which is structurally similar to BCL-G L [ 112 ]. A recently published report on BFK might shed light on the directions of further research on BCL-G [ 113 ]. Biophysical interaction analysis revealed that full-length BFK did not interact with other BCL-2-like proteins, but instead it was functionally reminiscent of BID, in which the BH3 domain was released upon caspase-mediated cleavage and truncated form (tBID) underwent a conformational alteration [ 113 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their traditional function of suppressing apoptosis, BCL-2 and BCL-XL have been shown to have a role in the regulation of other critical cellular processes, including proliferation, autophagy, differentiation, DNA repair, tumor growth, and angiogenesis via their BH4 domain [21]. The antiapoptotic and proapoptotic proteins contain four BH domains which take on a conserved functional group containing six or seven amphiphilic a-helices and two hydrophobic a-helices at the center to form a hydrophobic BH3 domain-binding cleft that works as a receptor for BH3 domains [17,22]. These four BH domain-containing (BH1-BH4) proteins inhibit apoptosis by interacting and trapping their pro-apoptotic counterparts [23].…”
Section: Introductionmentioning
confidence: 99%